1978
DOI: 10.1111/j.1600-0447.1978.tb06899.x
|View full text |Cite
|
Sign up to set email alerts
|

The dementia of dementia praecox

Abstract: A group of 18 long‐stay patients with a diagnosis of schizophrenia were compared with a group of 10 age‐matched subjects who had been institutionalized by reason of physical disease, on performance on tests of intellectual function; and with a group of agematched healthy subjects, both on tests of intellectual function, and radiographically, using the technique of computerized axial tomography (EMI scan) of the brain. By comparison with the normal controls the patients with schizophrenia had increased cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(83 citation statements)
references
References 24 publications
2
79
2
Order By: Relevance
“…Later however, general intellectual deficits in chronic schizophrenia were demonstrated by Johnstone et al (1978), who also suggested that the cognitive dysfunction was primary and not secondary to institutionalization or symptoms of the disease. Since then, a growing interest in the field and acknowledgment of its importance has emerged.…”
Section: Neurocognitive Functioning In Schizophrenia and Bipolar Disomentioning
confidence: 99%
“…Later however, general intellectual deficits in chronic schizophrenia were demonstrated by Johnstone et al (1978), who also suggested that the cognitive dysfunction was primary and not secondary to institutionalization or symptoms of the disease. Since then, a growing interest in the field and acknowledgment of its importance has emerged.…”
Section: Neurocognitive Functioning In Schizophrenia and Bipolar Disomentioning
confidence: 99%
“…1 However, his ideas were soon displaced by Kraepelin's conceptualization of dementia praecox as an adult onset neurodegenerative disorder, 2 a view which held sway for nearly a century. Indeed, in the late 1970s, when Johnstone et al 3,4 demonstrated that people with chronic schizophrenia had lateral ventricular enlargement and cognitive deficits, they interpreted their findings as confirming "the dementia of dementia praecox. "…”
Section: The Origins Of the Neurodevelopmental Hypothesismentioning
confidence: 99%
“…They are thought to be probably related to impairments in specific brain areas, such as the cerebellar (motor co-ordination), the temporal (sensory integration) and the frontal (complex motor acts). Similar widespread alterations have been supposed to be involved in the pathogenesis of schizophrenic negative symptomatology, often associated with cognitive deterioration, lateral ventricular enlargement and widespread brain abnormalities, suggesting a more 'organic' aetiology for this clinical dimension than for the others [34][35][36][37]. Finally, it seems that NSS frequently occur in conjunction with negative symptomatology [38][39][40][41] and chronic course of schizophrenia [31,[42][43][44], while they are relatively unaffected by neuroleptic treatment, having also been found in drug-free and first episode patients [45][46][47].…”
Section: Introductionmentioning
confidence: 99%